Pengaruh Kemiringan dan Jumlah Pisau Pencacah terhadap Kinerja Mesin Pencacah Rumput untuk Kompos - Mukhlis A. Hamarung; Jasman Jasman (Jurnal Engine: Energi, Manufaktur, dan Material, 2019)
Compost can occur by itself through natural processes, but the process takes a long time. The process of organic materials such as grass into compost can be accelerated by the process of being chopped into small pieces first, then mixed with microorganisms. The process of cutting or chopping grass will be faster if done with a chopper machine. The size of the grass's chops significantly affects the composting process. The smaller of the chops, the composting process will be faster because decomposing bacteria touch the surface area. The research aims to study the effect of the inclination and the number of chopper blades on the grass chopper machine's performance. One component that affects the results of a chopper is a blade. The initial stage of this study is to build a prototype chopper with blades made from high-speed steel (HSS). The process of data collection is based on the different blade inclinations, i.e., 0o, 5o, and 10o to the horizontal axis, and the different number of blades, i.e., 2, 3, and 4 with 3,339 rpm motor rotation. The chopping capacity of the machine is measured based on the weight and length of the chops. The results of testing with the same blade inclination and the different number of blades show that with four blades, the weight of the chops is greater, and the percentage of chops with lengths > 1.5 cm is lower. This happens because the frequency of cutting is greater. While the same number of blades, but with different inclination, the weight and percentage of chops with lengths > 1.5 cm tend to be similar due to changes in the cutting platform.